2008
DOI: 10.4315/0362-028x-71.8.1685
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Characterization of Salmonella in Bovine Lymph Nodes Potentially Destined for Use in Ground Beef†

Abstract: A potential source of pathogenic bacteria in ground beef is the lymphatic system, specifically the lymph nodes. Bacteria have been isolated from the lymph nodes of cattle at slaughter; however, most studies have dealt with mesenteric lymph nodes, which are not normally incorporated into ground beef. The objective of the current study was to determine the prevalence and multidrug-resistance status of Salmonella in bovine lymph nodes associated with lean and fat trimmings that might be utilized in ground beef pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
55
1
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 99 publications
(62 citation statements)
references
References 22 publications
(27 reference statements)
2
55
1
4
Order By: Relevance
“…The Salmonella strains found contaminating these carcasses were those of MDR Salmonella Typhimurium in one event and pansusceptible Salmonella Dublin in the other, both serotypes known for causing clinical illness in cattle. This observation prompted a comparison of the Salmonella serotypes reported in a number of studies, including serotypes found in ground beef (14,75,79), those isolated from cattle lymph nodes (8), and those found on final carcasses in this study, along with serotypes noted for being isolated from clinically infected cattle (21,22). The last group was identified from the Salmonella Surveillance Annual Summary reports for 2005 and 2006, which summarize the Salmonella strains isolated and serotyped from clinical cases of animal disease that were reported to the Centers for Disease Control and Prevention (CDC) and the National Veterinary Services Laboratory (NVSL) in those time periods.…”
Section: Discussionmentioning
confidence: 92%
“…The Salmonella strains found contaminating these carcasses were those of MDR Salmonella Typhimurium in one event and pansusceptible Salmonella Dublin in the other, both serotypes known for causing clinical illness in cattle. This observation prompted a comparison of the Salmonella serotypes reported in a number of studies, including serotypes found in ground beef (14,75,79), those isolated from cattle lymph nodes (8), and those found on final carcasses in this study, along with serotypes noted for being isolated from clinically infected cattle (21,22). The last group was identified from the Salmonella Surveillance Annual Summary reports for 2005 and 2006, which summarize the Salmonella strains isolated and serotyped from clinical cases of animal disease that were reported to the Centers for Disease Control and Prevention (CDC) and the National Veterinary Services Laboratory (NVSL) in those time periods.…”
Section: Discussionmentioning
confidence: 92%
“…A recent but growing body of evidence demonstrates that cattle lymph nodes commonly harbor Salmonella (20)(21)(22)(23) and that, when incorporated into ground beef, lymph nodes may contribute to the observed discrepancy between effective control on carcass surfaces and subsequent isolation from ground beef. A more complete understanding of the ecology of cattle and Salmonella is needed.…”
mentioning
confidence: 99%
“…La contaminazione delle carni da parte di batteri è responsabile di diverse migliaia di malattie alimentari ogni anno negli Stati Uniti (T. M. Arthur, et al, 2008). Il principale mezzo per ridurre e prevenire questo tipo di malattia consiste nell'identificare le fonti di contaminazione e minimizzarle o rimuoverle dal processo produttivo.…”
Section: Introduzioneunclassified
“…Tuttavia, anche dopo la realizzazione di questi interventi, batteri patogeni possono ancora essere isolati da alimenti quali la carne macinata: questo molto probabilmente evidenzia esistono altre fonti di contaminazione. Una possibile fonte di batteri patogeni per la carne bovina è il sistema linfatico ed in particolare i linfonodi (T. M. Arthur, et al, 2008;BarkocyGallagher, et al, 2003;Bonardi, Foni, Chiapponi, Salsi, & Brindani, 2007;Bosilevac, et al, 2004;Sofos, et al, 1999). Il sistema linfatico è coinvolto nelle funzioni immunitarie agendo con un meccanismo di filtrazione in grado di sequestrare batteri, virus e altri agenti estranei all'organismo al fine di permettere l'eventuale distruzione da parte dei linfociti.…”
Section: Introduzioneunclassified
See 1 more Smart Citation